The Impact of Covid-19 on the Macro Indicators: A Comparative Analysis for Oil, Gold, Exchange Rates and Wheat - TEKER, DILEK; Deniz, E. Asena (Archives of Business Research, 2021)
COVID-19, which occurred in Wuhan, China at the end of December 2019 and have affected the whole world, appears to have drastic effects on human health and economic stability. Economic activities related to global trade decreased with the spread of the epidemic and caused crisis both economically and financially. This virus, which is also a health crisis, has affected human life greatly due to uncertainty in the protection and treatment processes. Increasing numbers of cases and deaths negatively affect the economic progress globally and show that countries with intense epidemic are vulnerable. Not knowing how long the pandemic will last and how long economic activities will be restricted requires an economic precaution. If the pandemic is brought under control quickly, the return to normal economic life will happen quickly and thus all economic sectors, especially service sectors, will recover in a short time. If the process of controlling the pandemic is long, the destruction on economic growth and employment will be at higher levels. With the vaccine found, it is predicted that the normalization process will accelerate and the economy may recover. Increased studies examining the impact of the COVID-19 pandemic on financial markets and commodity markets will make it easier for both economists and financial actors in the future. In this study, the relationship between the daily number of cases of COVID-19 and brent oil, gold, EUR / USD and wheat prices were examined. After the natural logarithm of our variables was applied, it was determined whether they were static or not. ARDL test, Impact-Response Analysis and Variance Decomposition were performed according to the determined lag lengths. According to the results, ARDL test was performed because our data was not stationary according to the ADF test and cointegration was not found among the data. As a result of impact response analysis, shocks lose their effect in a short time.